ETHICAL LEADERSHIP OF EDUCATIONAL INSTITUTION ADMINISTRATORS AFFECTING EDUCATIONAL QUALITY OF SCHOOLS EXPANDING OPPORTUNITIES UNDER THE OFFICE OF NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA 4 - Damsamut, Thanchanok; Chanakul, Benjaporn; Chairueng, Nopparat (Journal of MCU Nakhondhat, 2023)
The purpose of this research was to study ethical leadership. study the quality of educational institutions A study of ethical leadership that affects the quality of educational institutions. and to study the development of ethical leadership that affects the educational quality of opportunity expansion schools. Primary Educational Service Area Office Nakhon Si Thammarat District 4. Used a survey research model, The sample group consisted of 234 teachers and educational personnel who received the Good Teacher Award without vices. Pearson's correlation coefficient and multiple regression analysis. The results showed that 1) Ethical leadership of school administrators Overall, it was at a high level. Good service with the highest mean, followed by being a good role model Ethical decision-making and credibility has the least average 2) Educational institute quality Overall, it was at a high level. quality of students The aspect with the highest average followed by the cooperation between schools, parents and communities. and administrative processes and management has the least average 3) Ethical Leadership of School Administrators Ethical decision-making and good service Affecting the quality of educational establishments of schools to expand opportunities Office of Nakhon Si Thammarat Primary Educational Service Area, Region 4 with statistical significance at the .01 level, with the predictive efficiency equal to .852. 4) A good executive must be a good role model for his subordinates. must behave act appropriately Behavior that demonstrates the ability to navigate reliable have a positive attitude to work honor others Which executives with morality, ethics and desirable characteristics will make their subordinates happy at work and successful in work make quality work.